Do protic ionic liquids and water display analogous behavior in terms of hammett acidity function? - Shukla, Shashi Kant; Kumar, Anil (Chemical Physics Letters, 2013)
We address an issue whether the strength of carboxylic acids in water is linear with respect to that in ionic liquids. Strength of carboxylic acids in water and different PILs using Hammett function (Ho) has revealed interesting linear correlation between the Ho function for all acids in PILs and PIL-water in spite of large structural and electronic differences. These observations suggest that different structural and electronic features of PILs and water behave analogously towards Ho. This linearity in Ho functions between PILs and PIL-water systems can be used to develop predictive method to calculate Ho values. (c) 2013 Elsevier B.V. All rights reserved.